Psychological and Sociocultural Influences on Pre-Purchase Behavior in the Pre-Owned Car Market - Soham Patel,; Jay Patel,; Jignesh Vidani, (Journal of Advanced Research in Public Policy and Administration, 2024)
The complex interactions between psychological and sociocultural elements that affect consumers' pre-purchase decisions in the used automobile market are examined in this study. The study explores individual attitudes, perceptions of dependability, trust, and brand loyalty as well as the influence of perceived risk and prior experiences on consumer decision-making by looking at both the cognitive and emotional elements. The study also looks into socioeconomic and cultural effects, taking into account how marketing tactics, peer opinions, social conventions, and cultural expectations affect consumers' preferences and decisions when buying used cars. The research employs a mixed-methods approach, integrating quantitative surveys and qualitative interviews, with the goal of presenting a comprehensive comprehension of these factors. This will enable marketers and policymakers to effectively navigate and address the dynamic changes in the pre-owned car market.